THE ECONOMIC IMPACT OF ARTIFICIAL INTELLIGENCE AND THE DILEMMAS SURROUNDING THE LABOUR MARKET - Noémi CSUNYÓ (Oradea Journal of Business and Economics)
The study focuses on the concerns and opportunities surrounding artificial intelligence. The research questions associated with the study focused on the economic impacts related to AI and the additional dilemmas that arise concerning the adaptation of AI. Therefore, the study discusses the beneficial effects of AI on the economy as a whole, the labour market, and specific processes. At the same time, concerns are raised about labour and security dilemmas, including job insecurity, fear of losing jobs, data distortions and false outcomes. The topic is considered to be highly up-to-date, with a particular focus on the opportunities and concerns related to the changing trends in the labour market, which is being researched by several authors in international academic fields. As regards the methodology, it is a theoretical, descriptive research aiming to examine and accurately describe the topic and its effects from multiple perspectives. It is essentially based on qualitative data already available, supported by quantitative statistical data and forecasts. The approach of the research is based on a joint analysis of economic and security dilemmas and opportunities, in combination with examples and case studies related to the topic. The study analyses the impacts in general terms; however, it can be concluded that the impacts appear differently depending on how governments and companies can exploit the potential of AI. Generally, society still relies excessively on interpersonal relationships, thus, the replacement of processes by artificial intelligence is still limited, regardless of the current level of technology.